2006
DOI: 10.1124/mol.105.018333
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ-Independent Repression of Prostate-Specific Antigen Expression by Thiazolidinediones in Prostate Cancer Cells

Abstract: In light of the potential use of the thiazolidinedione family of peroxisome proliferator-activated receptor-␥ (PPAR␥) agonists in prostate cancer treatment, this study assessed the mechanism by which these agents suppress prostate-specific antigen (PSA) secretion in prostate cancer cells. Two lines of evidence indicate that the effect of thiazolidinediones on PSA downregulation is independent of PPAR␥ activation. First, this thiazolidinedione-mediated PSA down-regulation is structure-specific irrespective of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…The finding that many indole derivatives, including diindoylmethanes, exhibited PPARg agonist activity (18, 25-28, 36, 37) raised the possibility that PPARg activation might contribute to the apoptosis-inducing effect of OSU-A9. Accordingly, we used an established PPRE-luciferase reporter assay (33) to assess the ability of OSU-A9 to transactivate PPARg in PC-3 cells. However, even at 20 Amol/L, OSU-A9 lacked appreciable activity in PPARg transactivation, whereas the PPARg agonist rosiglitazone induced significant activation of the reporter gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that many indole derivatives, including diindoylmethanes, exhibited PPARg agonist activity (18, 25-28, 36, 37) raised the possibility that PPARg activation might contribute to the apoptosis-inducing effect of OSU-A9. Accordingly, we used an established PPRE-luciferase reporter assay (33) to assess the ability of OSU-A9 to transactivate PPARg in PC-3 cells. However, even at 20 Amol/L, OSU-A9 lacked appreciable activity in PPARg transactivation, whereas the PPARg agonist rosiglitazone induced significant activation of the reporter gene (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PPAR-response element (PPRE)-x3-TK-Luc reporter vector contains three copies of the PPRE upstream of the thymidine kinase promoter-luciferase fusion gene and was kindly provided by Dr. Bruce Spiegelman (Harvard University, Cambridge, MA). The reporter gene assay was carried out as previously described (33). In brief, PC-3 cells were cultured in a 100-mm plate in phenol red-free RPMI 1640 containing 10% FBS until the achieved 50% to 70% confluency, after which they were transfected with 6 Ag of the plasmid using Fugene 6 (Roche) in RPMI 1640.…”
Section: Methodsmentioning
confidence: 99%
“…These results are in agreement with the study of Yang et al showing that 10 mM of D2-TGZ were sufficient to significantly reduce LNCaP prostate cancer cells viability after 24 h of treatment in serum-free conditions whereas no considerable effect was detected with up to 50 mM of D2-TGZ in 10% FCS conditions. 11 Thus, the reduced sensitivity of cells to D2-TGZ in high serum conditions is not restricted to breast cancer cells. Besides, a study reported that troglitazone, the parent molecule of D2-TGZ, activated the ERK pathway and induced p21 Cip/WAF1 in the colorectal cancer cell lines HCT15 and HT29 with a dose of 200 mM in 10% FBS-conditions, whereas 20 mM of TGZ were enough to induce these effects in 1% FBSconditions.…”
Section: Discussionmentioning
confidence: 99%
“…This attenuation of PPARg activity is explained by the structural rigidity induced by the double bond introduction surrounding the heterocycle system. 10,11 In breast cancer cell lines, the number of viable cells was reduced after exposure to D2-TGZ. 12 Such a treatment induced a proteasome-dependent proteolysis of both cyclin D1 and estrogen receptor a in hormone-dependent breast cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, data from this and other laboratories indicate that the peroxisome proliferator-activated receptor-g (PPARg) agonist troglitazone might interfere with AR function through two PPARg-independent mechanisms (15,16). At concentrations f10 Amol/L, troglitazone and its PPARg-inactive derivative D2TG repressed prostate-specific antigen (PSA) through the inhibition of AR recruitment to the PSA promoter.…”
Section: Introductionmentioning
confidence: 99%